2014
DOI: 10.1186/1471-2334-14-50
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of adenoviruses associated with respiratory infection in Egypt from 2003 to 2010

Abstract: BackgroundHuman adenoviruses of species B, C, and E (HAdV-B, –C, -E) are frequent causative agents of acute respiratory infections worldwide. As part of a surveillance program aimed at identifying the etiology of influenza-like illness (ILI) in Egypt, we characterized 105 adenovirus isolates from clinical samples collected between 2003 and 2010.MethodsIdentification of the isolates as HAdV was accomplished by an immunofluorescence assay (IFA) and confirmed by a set of species and type specific polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
19
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 44 publications
(52 reference statements)
8
19
6
Order By: Relevance
“…In addition to Beijing, these HAdVs were also most frequently detected from acute respiratory tract disease cases in other cities of China such as Guangzhou in Central South China [18] and Lanzhou City in Northeast China [19], which indicated that these HAdV types are widely distributed in China. This study is also consistent with reports from Argentina [20], USA [21], Egypt [22], and Korea [23].…”
Section: Discussionsupporting
confidence: 92%
“…In addition to Beijing, these HAdVs were also most frequently detected from acute respiratory tract disease cases in other cities of China such as Guangzhou in Central South China [18] and Lanzhou City in Northeast China [19], which indicated that these HAdV types are widely distributed in China. This study is also consistent with reports from Argentina [20], USA [21], Egypt [22], and Korea [23].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the group age, as expected, results showed that most patients with HAdV infection were younger than 5 years (62.2%), a statistically significant finding. These results are in concordance with those of other studies which findings concluded that most children are infected by adenovirus at an early age [25,37,[38][39][40][41]. Indeed, it is well established that by 5 years of age, 70% to 80% of children demonstrate antibodies to at least one serotype [42].…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, this is evidence that these two definitions produce physically different outbreaks and emphasizes the importance of taking definitions into account when comparing outbreaks. Given that it is known that influenza-like-illness outbreaks commonly include a number of viruses other than the flu, including adenoviruses and rhinovirus [ 32 34 ], and that Eick-Cost et al demonstrates low specificity within the DoD definition [ 6 ], it makes sense that the two definitions produce dissimilar outbreaks.…”
Section: Resultsmentioning
confidence: 99%